2022
DOI: 10.1186/s12966-022-01293-1
|View full text |Cite
|
Sign up to set email alerts
|

Clustering individuals’ temporal patterns of affective states, hunger, and food craving by latent class vector-autoregression

Abstract: Background Eating plays an important role in mental and physical health and is influenced by affective (e.g., emotions, stress) and appetitive (i.e., food craving, hunger) states, among others. Yet, substantial temporal variability and marked individual differences in these relationships have been reported. Exploratory data analytical approaches that account for variability between and within individuals might benefit respective theory development and subsequent confirmatory studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…All items were answered on a horizontal slider ranging from 0 (= ‘very little’/ ‘not at all’) to 100 (= ‘very much’/ ‘very’). EMA-items not included in the current analyses such as craving, hunger or affect are described elsewhere [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…All items were answered on a horizontal slider ranging from 0 (= ‘very little’/ ‘not at all’) to 100 (= ‘very much’/ ‘very’). EMA-items not included in the current analyses such as craving, hunger or affect are described elsewhere [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Participants included in the present secondary data analysis came from a larger randomized control trial (DRKS, DRKS00017493). 1 Other parts of the data have previously been used in the studies by Pannicke et al ( 19 ) and Kaiser and Butter ( 17 ). Participants were recruited to be motivated to maintain or reduce their body weight.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the present results are highly specific, for example, to the used "prediction interval" of 2.5 hours between predictors and outcome. This could be problematic as it has been shown that emotions and eating can influence each other at different time intervals [60].…”
Section: Limitations and Strengthsmentioning
confidence: 99%